MRI to Ultrasound Cognitive Targeted Prostate Biopsy Provides all the Benefit of Ultrasound Fusion Without the Increased Resources - Suderman, Jonathan D.; Mannas, Miles (Société Internationale d'Urologie Journal, 2023)
None.